Increased genetic vulnerability to smoking at CHRNA5 in early-onset smokers. - Hartz, S; Short, SE; Saccone, N; Culverhouse, R; Chen, L; Schwantes-An, T; Coon, H; Han, Y; Stephens, S; Sun, J; Chen, X; Ducci, F; et al. (2012)
CONTEXT: Recent studies have shown an association between cigarettes per day (CPD) and a nonsynonymous single-nucleotide polymorphism in CHRNA5, rs16969968. OBJECTIVE: To determine whether the association between rs16969968 and smoking is modified by age at onset of regular smoking. DATA SOURCES: Primary data. STUDY SELECTION: Available genetic studies containing measures of CPD and the genotype of rs16969968 or its proxy. DATA EXTRACTION: Uniform statistical analysis scripts were run locally. Starting with 94,050 ever-smokers from 43 studies, we extracted the heavy smokers (CPD >20) and light smokers (CPD ≤10) with age-at-onset information, reducing the sample size to 33,348. Each study was stratified into early-onset smokers (age at onset ≤16 years) and late-onset smokers (age at onset >16 years), and a logistic regression of heavy vs light smoking with the rs16969968 genotype was computed for each stratum. Meta-analysis was performed within each age-at-onset stratum. DATA SYNTHESIS: Individuals with 1 risk allele at rs16969968 who were early-onset smokers were significantly more likely to be heavy smokers in adulthood (odds ratio [OR] = 1.45; 95% CI, 1.36-1.55; n = 13,843) than were carriers of the risk allele who were late-onset smokers (OR = 1.27; 95% CI, 1.21-1.33, n = 19,505) (P = .01). CONCLUSION: These results highlight an increased genetic vulnerability to smoking in early-onset smokers.